2011
DOI: 10.1037/a0023194
|View full text |Cite
|
Sign up to set email alerts
|

Lay judgments about child custody after divorce.

Abstract: In a pair of studies, we examine lay people's judgments about how hypothetical cases involving child custody after divorce should be resolved. The respondents were citizens called to jury service in Pima County, AZ. Study 1 found that both male and female respondents, if they were the judge, would most commonly award equally shared custody arrangements, as advocated by most fathers' groups. However, if the predivorce child care had been divided disproportionately between the parents, this preference shifted, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 43 publications
(43 reference statements)
4
34
0
3
Order By: Relevance
“…In a 2004 nonbinding ballot election in Massachusetts, 85% of the voters (530,000 people) said that children should live with each parent equally after divorce (Fatherhood Coalition, 2004). Other surveys in Arizona of college students and other adults also found that 80% to 90 % believe in shared residential parenting after divorce (Braver, Ellman, Votruba, & Fabricius, 2011). In an even more recent survey of 375 people who had been called for jury duty, 67% said they favored shared residential parenting .…”
Section: Abstract Joint Physical Custody Parenting Plans Shared Parmentioning
confidence: 97%
“…In a 2004 nonbinding ballot election in Massachusetts, 85% of the voters (530,000 people) said that children should live with each parent equally after divorce (Fatherhood Coalition, 2004). Other surveys in Arizona of college students and other adults also found that 80% to 90 % believe in shared residential parenting after divorce (Braver, Ellman, Votruba, & Fabricius, 2011). In an even more recent survey of 375 people who had been called for jury duty, 67% said they favored shared residential parenting .…”
Section: Abstract Joint Physical Custody Parenting Plans Shared Parmentioning
confidence: 97%
“…Dans le même ordre d'idées, une recherche (Braver et al, 2011) montre que la population en général croit majoritairement que le système de justice est biaisé en faveur des mères. Selon Braver et ses collaborateurs, cette perception pourrait avoir un impact sur les ententes que les parents prennent à la suite d'une séparation en évaluant la probabilité de gagner leur cause s'ils se présentent en cour.…”
Section: Quelles Sont Les Caractéristiques Des Situations Expertisées Ouunclassified
“…Il y a fort à parier que le modèle de pérennité a pris davantage d'importance, c'est du moins le point de vue d'auteurs qui soulèvent l'existence d'un courant fort en faveur de la garde partagée dans la jurisprudence (Goubau, 2003;Tétrault, 2006). Ce mouvement semble aller de pair avec l'opinion générale de la population (Braver et al, 2011;Saint-Jacques et al, 2013). En effet, un sondage représentatif de la population du Québec révèle un appui très majoritaire à la garde partagée après une séparation pour les enfants âgés de plus de deux ans (SaintJacques et al, 2013).…”
Section: Quelles Sont Les Caractéristiques Des Situations Expertisées Ouunclassified
“…En relación a esto, se puede apreciar que es el varón el que los inicia en mayor medida en comparación con la mujer tanto en 2011, como en 2012. Estos resultados se justifican porque mediante estas modificaciones (realizadas en mayor medida cuando existen hijos/as), se pretende variar sobre todo sentencias relativas a los derechos y deberes para con los regímenes de convivencia de los menores (De Blasio y Vuri, 2013); que hasta no hace mucho tiempo se fallaban en mayor medida a favor de la madre (Bauserman, 2002;Braver, Ellman, Votruba y Fabricius, 2011;Fabricius, Braver, Diaz, y Velez, 2010;Ordóñez y Couto, 2012). Por otra parte, se destaca también el ligero aumento de la presentación conjunta de esta demanda de modificación de medidas.…”
Section: Conclusionesunclassified